Shape-Based Matching: Application of Defect Detection - Sulaiman , Marizan; Mohd Shah, Hairol Nizam (2011)
This research regrading to the application of a vision algorithm sensor to monitor the operation of a system in order to control the concerning jobs and work pieces recognition that are to be made during system operation in real time.